Partial reconstitution of the prophenoloxidase activation system in Anopheles gambiae - Chunxiang Hou; Yang Wang; Haobo Jiang (Proceedings of the National Academy of Sciences, 2026)
Melanization is a central insect immune response to wounding and microbial invasion. It is mediated by a system of serine proteases and their homologs, mostly members of the CLIP subfamily, and leads to prophenoloxidase (proPO) activation and PO-mediated production of cytotoxic compounds and melanin polymers that kill and sequester invading pathogens. In mosquitoes, melanotic encapsulation provides an effective defense against malaria parasites, yet the composition and organization of the underlying serine protease system remain largely unclear. Guided by gene orthology and protein abundance, we expressed SP217, four CLIPCs, and 12 CLIPBs from Anopheles gambiae and reconstructed a five-step branched cascade using purified zymogens. SP217, an ortholog of Drosophila ModSP, initiates the cascade by activating proCLIPC1. CLIPC1 activates proCLIPB13 and proCLIPB47, two of the 10 orthologs of Drosophila Grass and Manduca HP5. CLIPB13 activates proCLIPC4, proCLIPC6, and proCLIPB10 whereas CLIPB47 activates proCLIPC6 only. In the next step, CLIPC6 activates proCLIPB4 and proCLIPB9. CLIPB9 and CLIPB10 function as proPO-activating proteases (PAPs), cleaving proPO2 to generate highly active PO2 in the presence of a cofactor. Together, these results have revealed a framework of the mosquito serine protease system that drives melanization. Our findings highlight both strong evolutionary conservation of the system among holometabolous insects and species-specific differences in its organization, providing a foundation for future analysis through combinational genetic perturbation.